Rational emotive behaviour therapy a reader - Dryden, Windy (SAGE, 1995)
This practically oriented reader brings together the major writings of the past decade on rational emotive behaviour therapy (REBT). It is most famous for the ABC analysis which helps clients to understand that irrational beliefs underpin their disturbed emotions and actions and that by disputing those beliefs they can change their behaviour. Originally called rational-emotive therapy (RET), it is also closely